Ethics and technology : ethical issues in an age of information and communication technology - Tavani, Herman T. (John Wiley, 2007)
Offering insights and coverage of the field of cyber-ethics, this book introduces readers to issues in computer ethics. The author combines his years of experience in the field with coverage of concepts and real-world case studies.